Preliminary observations of necrophagous dipteran activities and a new host record of parasitoids on a high-rise building - Heo, C.C.; Latif, B.; Kurahashi, H.; Tan, S.H.; Chew, W.K.; Nazni, W.A.; Omar, B. (De Gruyter Open, 2017)
A preliminary study on the ecological activities of necrophagous Diptera on a high-rise building in Malaysia was conducted from April to August 2010. Fresh chicken livers (approximately 500 g) serving as bait were placed on the rooftop (101.6 m from the ground). Three replicates were carried out, each replicate lasting 30 days with daily observations and fly sampling. Maggots found in the bait were collected at random: some were preserved in 70% ethanol while the others were reared to the adult stage. Results showed that the flies arrived on the bait between 8 hours and 3 days after placement. The oriental latrine blow fly Chrysomya megacephala (Diptera: Calliphoridae) was the first to reach this altitude, followed by the scuttle fly Megaselia scalaris (Diptera: Phoridae) and the flesh fly Liopygia ruficornis (Diptera: Sarcophagidae). The larvae of Chrysomya megacephala were first recovered from the bait. However, they were succeeded by sarcophagid larvae. The predominant sarcophagid larvae were then raised to the adult stage and the resulting adults were identified as Parasarcophaga dux. The other sarcophagid pupae were either parasitized by hymenopteran parasitoids or dead. We recorded two species of parasitoids emerging from Liopygia ruficornis pupae: Exoristobia philippinensis (Hymenoptera: Encyrtidae) and Dirhinus himalayanus (Hymenoptera: Chalcididae). Liopygia ruficornis is recorded as a new host for these parasitoids for the first time.